Pengaruh Penempatan Kerja Dan Motivasi Karyawan Terhadap Kinerja Karyawan Di PT. Yamaha Musical Products Indonesia - Shega Erik Wicakosno; Hadi Sunaryo; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine the effect of work placement and motivation on the performance of employees of PT. Yamaha Musical Products Indonesia. The Covid-19 pandemic has had many impacts in various fields, including work placements and employee motivation within the company. PT Yamaha Musical Products Indonesia experienced a decline in employee absenteeism during the Covid-19 pandemic. The method used in this research is quantitative descriptive analysis method and statistical analysis method using Multiple Regression Test. the results of this study indicate a significant influence of work placement and employee motivation on employee performance. Partially, job placement has no effect on employee performance. Partially, employee motivation has an effect on company performance. Keywords: Work Placement, Motivation, Employee Performance